2019
DOI: 10.1016/j.foodres.2019.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of volatile fingerprint by HS-SPME/GC-qMS and E-nose for the classification of cocoa bean shells using chemometrics

Abstract: Cet article publié par ELSEVIER provient du Dépôt institutionnel de l'Université Libre de Bruxelles, DIfusion http://difusion.ulb.ac.be. Il n'est accessible qu'aux membres de la communauté universitaire de l'ULB sur le réseau sécurisé de l'ULB. Tout utilisateur autorisé peut lire, télécharger ou reproduire cet article à des fins d'usage privé ou à des fins non commerciales d'enseignement ou de recherche scientifique. Il ne peut être atteint à l'intégrité de l'article, et les noms des auteurs et de l'éditeur do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…Among its multiple applications, CBS have been largely proposed as clean label ingredients and/or additives because of the nutraceutical character that their high fiber and polyphenol contents provide. Besides, some studies have shown that CBS possess between 10% and 20% of the total amount of volatile organic compounds found in roasted cocoa beans (Table 1), many of them being key aroma compounds for cocoa and chocolate [31,68]. This makes CBS a very interesting, low-cost ingredient for cocoa substitution or cocoa flavoring.…”
Section: Food Applicationsmentioning
confidence: 99%
“…Among its multiple applications, CBS have been largely proposed as clean label ingredients and/or additives because of the nutraceutical character that their high fiber and polyphenol contents provide. Besides, some studies have shown that CBS possess between 10% and 20% of the total amount of volatile organic compounds found in roasted cocoa beans (Table 1), many of them being key aroma compounds for cocoa and chocolate [31,68]. This makes CBS a very interesting, low-cost ingredient for cocoa substitution or cocoa flavoring.…”
Section: Food Applicationsmentioning
confidence: 99%
“…It also has a low fat content with physical and chemical characteristics identical to those of cocoa butter except for linoleic acid, which is higher in the CBS (7.49% in CBS fat vs. 3.93% in cocoa butter) [2,4]. Moreover, the CBS is also a source of dietary minerals (e.g., calcium, iron, and magnesium) [5] and key aromatic compounds (e.g., 3-methylbutanal and 2,3,5-trimethylpyrazine) that contribute to its cocoa flavour notes [6,7]. Finally, the CBS contains a high number of polyphenols with a total phenolic content that ranges from 3.12-94.95 mg of gallic acid equivalents (GAE)/g of dried CBSs mainly resulting from flavanols, which include catechins, epicatechins, and procyanidins [3].…”
Section: Introductionmentioning
confidence: 99%
“…CBS constitutes 10-17% of the total cocoa bean weight and is normally discarded after its separation from roasted cocoa beans, entailing economic and environmental issues since more than 700,000 tons of CBS is estimated to be produced yearly around the world [7]. Nevertheless, CBS has demonstrated to be an interesting food ingredient since it has a similar nutritional composition to that of cocoa nibs (except for the fat content, which is substituted by fiber in the case of CBS) [7] and a similar aromatic profile to that of cocoa powder [8,9]. However, what attracts more attention in scientific research and adds value to this cocoa by-product is its content in dietary fiber, which ranges from 39.3% to 66.3%, and polyphenols, mainly flavanols [7].…”
Section: Introductionmentioning
confidence: 99%